Islam dalam Masyarakat Perkebunan: Dinamika Keagamaan Masyarakat Transmigran di Bengkulu - Moch Iqbal (Institut Agama Islam Negeri Bengkulu, 2020)
This study aims to determine the religion of the transmigrant community in Bengkulu, precisely in the Abu Syakim Village, Pondok Kelapa District, North Bengkulu. Known Bengkulu is one of the areas where transmigrants from Java and Bali are located. The migrants then interacted with the new environment which produced unique variants. This research method is qualitative with a case study approach. The research data, which mostly used the subject's words, both spoken and written, were obtained from two kinds of sources, namely the author and several other informants. Data collection activities were carried out using in-depth interviews, passive role observation and documentation methods. Using Weber's concept of 'the disenchanment of the world', which will help analyze findings in the field. The results of the study were: first, there was a 'plagiarism' of Javanese culture and religious traditions, which were brought to the transmigration area of Bengkulu. Moreover, its economic activities are still land-based, although the pattern is somewhat different, namely from lowland rice to plantations. Second, the tarekat activities will grow and develop. There are at least two orders in the village of Abu Syakim, namely the Qodariyah Naqsabandiyah order and the Shiddiqiyah tarekat. Both orders are also led by immigrants.